Receiving Enzyme Replacement Therapy for a Lysosomal Storage Disorder: A Preliminary Exploration of the Experiences of Young Patients and Their Families. Issue 4 (28th March 2013) - Freedman, R.; Sahhar, M.; Curnow, L.; Lee, J.; Peters, H.
Abstract: Medical intervention for lysosomal storage disorders becomes part of life, shaping the reality of the condition for affected individuals and families. Enzyme replacement therapy (ERT) is available to treat some lysosomal storage disorders. ERT is costly and time consuming, requiring frequent hospital visits to receive intravenous infusions. This qualitative study sought to explore the impact of receiving ERT for a lysosomal storage disorder on the health related quality of life (HRQoL) of young patients and their families. Fifteen semi–structured interviews were conducted with young people and parents and siblings of young people accessing ERT for Pompe disease, Gaucher disease or mucopolysaccharidosis types I or II living in Victoria, Australia. Interviews were transcribed then analyzed thematically. The biopsychosocial model assisted in interpreting themes. Findings revealed positive attitudes towards ERT, with noticed improvements in physical and psychosocial well‐being. Participants prioritised intervention over other activities and provided suggestions for improving current service delivery. Communication with family members and professionals was deemed important, especially in respect to information provision. Participants described challenges associated with living with a lysosomal storage disorder and receiving ERT and coping strategies, such as positive thinking and ways to manage uncertainty. These findings provide valuable insights into the impact of living with a chronic genetic condition and receiving intensive treatment on HRQoL.